PP8 Sedentary behaviour and physical activity patterns of urban adolescents: a study using ecological momentary assessment. (21st October 2014) - Marques, A; André, J; Martins, J; Sarmento, H; Diniz, J; da Costa, FC
Abstract : Understanding the relationship between sedentary behaviours (SB) and physical activity (PA) may lead to the development of effective intervention programs to promote active lifestyles. This study aimed to examine the prevalence and clustering of SB and PA among urban Portuguese adolescents. The study comprised a total of 651 adolescents (378 girls) aged 12–14. Ecological Momentary Assessment was used to measure SB and PA, using 15 min time intervals. To identify gender differences t test was used. Cluster analyses were performed using the most prevalent SB and PA, separately for boys and girls. Television (TV) viewing was the most consuming leisure time (boys 98 min/day, girls 60 min/day), followed by computer use (boys 43 min/day, girls 22 min/day), and talking with friends (boys 11 min/day, girls 31 min/day, p < 0.001). Boys devoted significantly more time on screen-time and talking than girls (p < 0.001). Boys practiced 41 min/day and girls 24 min/day (p < 0.001) of sport activities. Based on these behaviours three cluster solutions were found both for boys and girls. Boys who spent more time watching TV and on the computer, spent less time studying, talking and doing PA (n = 70). Boys who devoted more time to PA watched more TV and spent less time on the computer, studying and talking (n = 56). Girls whose leisure time was dominated by talking with friends watched less TV and did less PA (n = 49). The most active girls dedicated less time to studying, viewing TV, using the computer and talking with friends (n = 105). Boys (n = 147) and girls (n = 224) who studied more spent less time watching TV, using the computer, talking with friends and doing PA. Findings from the study suggest a need for diverse behavioural targets in interventions design to reduce time devoted to sedentary behaviours and increasing physical activity in sub groups of adolescents.